2003
DOI: 10.1063/1.1571234
|View full text |Cite
|
Sign up to set email alerts
|

Effect of strain rate on the formation of nanocrystallites in an Al-based amorphous alloy during nanoindentation

Abstract: The effect of deformation by nanoindentation on nanocrystallization in amorphous Al 90 Fe 5 Gd 5 was investigated by transmission electron microscopy. Massive precipitation of nanocrystallites is observed within the indents. Under the quasistatic condition used, a temperature rise due to adiabatic heating is likely negligible, confirming that plastic deformation can induce crystallization without a heating effect. The nucleation of nanocrystallites is significantly affected by the strain rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 19 publications
2
42
0
1
Order By: Relevance
“…The results indicated that mechanical deformation at or near room temperature led to the precipitation of nanocrystalline Al. 10 Furthermore, our work also demonstrated that the stress state is an important factor in mechanically induced nanocrystallization of an amorphous alloy. Nanocrystallization occurred only in the predominantly compressive region of a sample bent at room temperature.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…The results indicated that mechanical deformation at or near room temperature led to the precipitation of nanocrystalline Al. 10 Furthermore, our work also demonstrated that the stress state is an important factor in mechanically induced nanocrystallization of an amorphous alloy. Nanocrystallization occurred only in the predominantly compressive region of a sample bent at room temperature.…”
Section: Introductionmentioning
confidence: 74%
“…12 Mechanically induced nanocrystallization appears to be a general phenomenon, since it has been observed in Al-, Zr-, and Fe-based alloys. [1][2][3][4][5][6][7][8][9][10][11][12] However, this process is composition dependent; it may vary between otherwise similar alloys. 1,4 Mechanically induced nanocrystallization occurs exclusively at shear bands, which are the main microstructural response to plastic deformation in amorphous alloys.…”
Section: Introductionmentioning
confidence: 99%
“…29,30) For the deformation-induced crystallization, no alignment of crystallographic directions of crystallites has been reported and it has been claimed that plastic-deformation-assisted atomic transport is responsible for the precipitation of nanocrystallites. A computer simulation work on plastic deformation of metallic glass 16) has shown that the amorphous structure is composed of the relatively lower dense region and the relatively higher dense region and the enhancement of diffusional mobility takes place in inside of deforming shear bands associated with relatively low density region.…”
Section: Discussionmentioning
confidence: 99%
“…Uniaxial tensile loading can effect large changes in atomic spacing and chemical bonding patterns, providing a powerful technique to probe amorphous alloys. Although some recent works have revealed the variables that affect amorphous systems of different elemental compositions [9][10][11][12] , the relation between local structure and uniaxial tensile strain for ternary amorphous alloys is only seldom reported 13) .…”
Section: Introductionmentioning
confidence: 99%